Study of wear process of estimated temperature distribution on surface of working bodies of tillage tools (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
Based on the analysis of literary sources and modern trends in soil cultivation, methods of strengthening and restoring ploughshares have been developed. Strengthening was carried out by applying reinforcing rollers to the cutting surface. Restoration was carried out by the method of placing compensating inserts to obtain a serrated working surfaceIt is proposed to analyse the surface wear of ploughshares by changing the temperature of the cutting part in contact with abrasive soil particles. A thermal imager was used for the analysis; the surface was examined after 0.5 ha.During the analysis, it can be seen that the temperature on the working surface of the ploughshare increases with the increase in working time. In the zones of the greatest impact of the abrasive, the temperature is increased. The intensity of heat generation depends on the work of friction and the dimensions of the site on which it occurs. The work done by an external force against the forces of friction is converted into heat and is used to heat the rubbing bodies. During the analysis, it can be seen that the temperature on the working surface of the ploughshare increases with the increase in working timeFor further research, it is necessary to conduct a study with a working area of 20 ha. Enterprises of the Kharkiv region plan to plow in the autumn period, for which it was agreed to use strengthened and restored ploughshares.
Keywords: ploughshare; restoration; strengthening; friction; thermal imager; hard work